2011
DOI: 10.1519/jsc.0b013e318201bf48
|View full text |Cite
|
Sign up to set email alerts
|

Do Force–Time and Power–Time Measures in a Loaded Jump Squat Differentiate between Speed Performance and Playing Level in Elite and Elite Junior Rugby Union Players?

Abstract: The purpose of this study was to investigate the discriminative ability of rebound jump squat force-time and power-time measures in differentiating speed performance and competition level in elite and elite junior rugby union players. Forty professional rugby union players performed 3 rebound jump squats with an external load of 40 kg from which a number of force-time and power-time variables were acquired and analyzed. Additionally, players performed 3 sprints over 30 m with timing gates at 5, 10, and 30 m. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 20 publications
9
29
1
Order By: Relevance
“…Interestingly Barr et al, [19] found no significant differences between senior and U20s internationals for initial and maximal sprint velocity, however, when initial and maximal sprint momentum was calculated there were significant differences between the groups. These findings are further corroborated by the work of Hansen and colleagues [23] who reported significant differences between elite senior and junior players for mass and measures of strength and power, but not for speed times over 5, 10 and 30m.…”
Section: Introductionsupporting
confidence: 82%
“…Interestingly Barr et al, [19] found no significant differences between senior and U20s internationals for initial and maximal sprint velocity, however, when initial and maximal sprint momentum was calculated there were significant differences between the groups. These findings are further corroborated by the work of Hansen and colleagues [23] who reported significant differences between elite senior and junior players for mass and measures of strength and power, but not for speed times over 5, 10 and 30m.…”
Section: Introductionsupporting
confidence: 82%
“…Different levels of strength exist ranging from submaximal to maximal, with maximal strength being a major factor influencing performance (57). Research has shown that stronger athletes are found at higher levels of competition in a variety of sports compared with weaker athletes (4,9,25,27,30). This information begins to illuminate the importance of maximal strength in sports competition.…”
Section: Maximal Strengthmentioning
confidence: 99%
“…However, multiple studies have shown that the average power output for the duration of a distance event, and even peak power during the final sprint, may play a critical role in determining the outcome of a race (42,44,58). Additionally, literature exists suggesting that levels of peak power outputs can differentiate athletic performance (4,6,7,9,21,25,30). As such, the development of muscular power is critical across the spectrum of sport from aerobic to anaerobic sports.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hansen et al (33) reported that peak power outputs are significantly (p , 0.001) higher in Elite Rugby Union players compared with their junior counterparts. Similarly, Baker (4) suggested that professional Rugby League players (National Rugby League) produce significantly higher power outputs in both upper-and lower-body movements compared with college-aged players (Student Rugby League).…”
Section: Introductionmentioning
confidence: 99%